Factors that contribute in customer loyalty at AIA Bhd. Headquarters, Kuala Lumpur / Nur Adena Izati Mohammad - Mohammad, Nur Adena Izati (Faculty of Business and Management, 2017)
This research is conducted to identify the factors that contribute in customer loyalty at AIA Bhd. headquarters, Kuala Lumpur. The factors are selected is customer perceived quality and expectations, customer trust and willingness and insurer commitment. The results of this research are based on these four objectives. First is to identify a positive relationship between customer perceived quality and expectations with customer loyalty. Second is to examine the relationship between customer trust and willingness with customer loyalty. Next, to identify the relationship between insurer commitments with customer loyalty and lastly, to identify the most influence factor in formation of customer loyalty. Data was gathered through questionnaire from customers of AIA Bhd. (n=96) located in Kuala Lumpur. Then, the data are analysed using SPSS (Statistical Package for the Social Sciences) version 20.0. The findings show that the three (3) variable customers perceived quality and expectations, customer trust and willingness and insurer commitments were important in determining influencing the loyalty of customer, therefore, AIA Bhd. headquarters, Kuala Lumpur need to consider these factors and provide the best way to improve customer loyalty among the customers.